Lynching and States of Fear in Urban Mexico - Binford, Leigh; Churchill, Nancy (Anthropologica, 2022)
On 23 November 2004 people in San Juan Ixtayopan, an urban community of Mexico City, lynched three agents of the Federal Preventative Police, accused of attempting to kidnap children attending the Popul Vuh elementary school. This article discusses how the state assumed a "law-and-order" approach to the lynching, missing an opportunity to interrogate critically the broader impact of neoliberal policies. While any particular lynching is the partial product of social and historical relationships on local social fields, neoliberal political economy establishes a broad context for grasping the recent spate of lynchings in Mexico and elsewhere in Latin America.